Early-stage design and development of mine waste valorisation technologies with expert input: a case study of South African sulfide-enriched coal waste - Stander, Helene-Marie (Department of Chemical Engineering, 2024)
Mining and minerals beneficiation typically result in the production of both valuable products and large bodies of waste, which are traditionally disposed of on land and carry environmental and social risks. Circular economy and resource efficiency trends have shifted the focus from disposal to waste reuse and recycling. Despite the benefits of the circular economy approach, development and implementation of waste reuse technologies in the mining industry is fraught with challenges and has thus far been limited. When designing processes for the application of large-volume mine waste, information deficits are encountered. This is largely because the characteristics of mine waste tend to be poorly understood or unknown as well as highly complex due to residual target minerals and processing chemicals present in the gangue components. Furthermore, whilst the technologies used may not be novel, their application in the processing of wastes is generally untested or inadequately researched. Working within such a context, with many unknowns, makes selection of appropriate technologies difficult. Another potential difficulty associated with designing and developing technologies for waste reuse is that unsolicited novel technologies by universities and research institutions can face opposition upon implementation. When designed and developed processes remain unimplemented, research resources are wasted and an opportunity to effect much-needed change is missed. It is these challenges that this study seeks to address through the development of a generalised systematic approach for the early-stage design and development of technologies for the reuse of mineral beneficiation waste that addresses both technology transfer and information deficit issues. The approach is based on three key premises: firstly, that technology transfer issues should be identified and integrated into technology selection and development from the early design and development stages. Secondly, that expert interviews and surveys can provide data that is useful not only in social sciences, but also in technical development and decision making to address data gaps. The third premise is that pre-feasibility studies, usually used to assess the techno-economics of relatively mature technologies, can be valuable for both technical information gathering and identifying technology transfer issues within the context of early-stage mineral processing waste reuse design and development. The application of this approach has been demonstrated in a case study on the downstream utilisation of South African sulfide-enriched fine coal processing waste. The premises identified above were studied in turn. Firstly, technology transfer issues were investigated using interviews with South African coal industry participants and the transcripts were analysed using thematic analysis. Secondly, the use of surveys and expert interviews to overcome data gaps in decision support for technology selection was investigated using a value theory multi-criteria decision analysis approach, and the data quality was assessed using distinguishability analysis. Lastly, the pre-feasibility study was conducted to assess the selected technology based on local contextual factors identified during the technology transfer interviews. The results of the study showed that exploring technology transfer issues in the early stages of technology development can support technology development by identifying aspects of key importance to the receiving industry. In terms of the case study, aspects such as the continued pre-eminence of techno-economic considerations in technology investment decisions and industry preference for mature technologies were identified. It was also highlighted that the South African mining industry is structured to focus on core business-related activities, making them unlikely to become technology development partners. Original equipment manufacturers and boutique waste processors, as opposed to mining companies, were considered appropriate commercial partners for universities and research institutions developing mine waste valorisation technologies. The study also showed that using expert judgement inputs as data for decision support must be done with caution. The case study data showed a high degree of dispersion to the point where the performance of technology alternatives on different criteria could not be meaningfully distinguished. Distinguishability improved with a more careful selection of “high-quality” experts and again when interviews were conducted with these experts, but not to the point of enabling defensible decision support. Analysis of the interview transcripts also showed that much of the variability could be attributed to uncertainty inherent in the decision problem as well as disagreement between experts. This indicated that some measure of variability in the data is inherent. Experts did, however, provide information that is useful for future technology development as well as indications of what research questions were still unanswered. Expert interviews for eliciting technical information therefore have value for providing background information for further development. Despite the uncertainties in the data, the option of using the sulfide-enriched coal processing waste as a soil ameliorant was consistently highly ranked and was therefore explored in the pre-feasibility study. The study also showed that technology viability can be assessed relatively efficiently using a prefeasibility study that incorporates consideration of technology transfer issues and local contextual issues. For the specific case study of application of sulfide-enriched fine coal processing waste as a soil ameliorant within the South African context, several issues were investigated: potential markets were identified; the transport costing of the product compared with the current market alternative was calculated; technical viability was assessed through a literature study; and health and safety risks were identified. This showed that while the technology is likely to be technically viable, the commercial viability is affected by high transport costs. The business case for the solution is therefore dependent on the avoided disposal costs for mines as well as the propensity of the material to slow-release acidity and thereby avoid repeated applications of the competitor product. In conclusion, this study demonstrated that a systematic and integrated approach for the early-stage design and development of waste valorisation technologies can help universities and research institutions structure the technology development process aiming at implementation of technologies. Ultimately, it is postulated that such an approach will facilitate the sustainable management of large-volume mineral beneficiation waste in line with the principles of industrial ecology and circular economy. Due to the difficulty with obtaining high-quality data for technology selection, it is recommended that improved approaches for early-stage technology selection must be investigated. Future work should furthermore include a more detailed investigation to clarify the cut-off distinguishability index values needed for different decision-analysis scenarios. Improved approaches for alternative identification in a mine waste valorisation context must also be investigated. Lastly, the role and approach of technical interviews, other technology transfer activities, and commercial partner identification must receive future research attention to investigate to what extent these can be combined to reduce resource requirements.